Circulating tumor DNA – A potential aid in the management of chordomas - Frederico, Stephen C.; Darling, Corbin; Zhang, Xiaoran; Huq, Sakibul; Agnihotri, Sameer; Gardner, Paul A.; Snyderman, Carl H.; Wang, Eric W.; Zenonos, Georgios A. (Frontiers in Oncology, 2022)
Chordomas are a locally invasive, low-grade, CNS malignancy that are primarily found in the skull base, spine, and sacrum. They are thought to be derived from notochordal remnants and remain a significant clinical challenge due to their local invasiveness, resistance to chemoradiation, and difficulty in achieving a complete resection. Adjuvant therapy such as proton beam therapy is critical in preventing recurrence in patients who are at high risk, however this treatment is associated with increased risk of complication. Currently, intraoperative observation and imaging findings are used to determine recurrence and success of gross total resection. These methods can be unreliable due to limited operative view, bony and soft tissue involvement, and complex post-operative changes on MRI. Earlier detection of incomplete resection or recurrence will allow for earlier ability to intervene and potentially improve patient outcomes. Circulating-tumor DNA (ctDNA) is cell-free DNA that is released by tumor cells as they undergo cellular turn-over. Monitoring ctDNA has been shown to be more sensitive at predicting residual tumor than imaging in numerous solid malignancies. Furthermore, ctDNA could be detected earlier in peripheral blood as opposed to imaging changes, allowing for earlier intervention. In this review, we intend to give a brief overview of the current state of molecular diagnosis for skull base chordomas. We will then discuss current advances in the utilization of ctDNA for CNS pathologies such as glioblastoma (GBM) and brain metastases. Finally, we will discuss potential implications of ctDNA monitoring for chordoma management.